PENGARUH UKURAN PEMERINTAH DAERAH, KEMAKMURAN, INTERGOVERNMENTAL REVENUE, TEMUAN DAN OPINI AUDIT BPK PADA KINERJA KEUANGAN - Masdiantini, Putu Riesty; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
The purpose of this study was to determine the effect of local government size, wealth, intergovernmental revenue, BPK audit findings and opinion on the financial performance of regency/city in Bali. The sample in this study was the regional government of 8 regencies and one city in the province of Bali with saturated sampling method. Data was collected by using nonparticipant observation method. Data analysis technique used was multiple linear regressions. The result of analysis showed that local government size and BPK audit opinion have significant and positive effect on the financial performance of the regency/city in Bali. On the other hand, other variables such as wealth, intergovernmental revenue and BPK audit findings do not affect financial performance of the regency/city in Bali.
Keywords: local government, audit, financial performance